Selenium concentrations in elderly people with Alzheimer's disease: a cross-sectional study with control group - Carlos Queiroz do Nascimento; João Araújo Barros-Neto; Nathalia Fidelis Lins Vieira; José Antonio Menezes-Filho; Sabrina Joanny Felizardo Neves; Sonia Oliveira Lima
ABSTRACT Objective: To investigate possible differences in plasma and erythrocyte concentrations of selenium among elderly with and without a diagnosis of Alzheimer's disease (AD). Methods: Cross-sectional study, performed with an elderly group with Alzheimer's disease, diagnosed by a geriatric doctor, and compared to an elderly group without the disease, equaling gender, education, and age. Atomic absorption spectrophotometry determined plasma and erythrocyte concentrations of total selenium (Set). Results: The mean age was 74.41±7.1 years in the Alzheimer's disease group and 71.46±5.1 years among the control group. The Alzheimer's disease group presented lower plasma concentrations (mean of 45.29±14.51 µg/dL vs. 55.14±14.01 µg/dL; p=0.004), and erythrocyte Set (median of 56.36 µg/L vs. 76.96 µg/L; p<0.001). The logistic regression model indicated an association between erythrocyte Set concentrations and diagnosis of Alzheimer's disease (p=0.028). Conclusion: Elderly with Alzheimer's disease present lower selenium concentrations in the evaluated organic compartments.